3-D cephalometry of the the orbit regarding endocrine orbitopathy, exophthalmos, and sex. - Konstantin Volker Hierl; Matthias Krause; Daniel Kruber; Ina Sterker (PLoS ONE, 2022)
Purpose This study aimed at evaluating the orbital anatomy of patients concerning the relevance of orbital anatomy in the etiology of EO (endocrine orbitopathy) and exophthalmos utilizing a novel approach regarding three-dimensional measurements. Furthermore, sexual dimorphism in orbital anatomy was analyzed. Methods Orbital anatomy of 123 Caucasian patients (52 with EO, 71 without EO) was examined using computed tomographic data and FAT software for 3-D cephalometry. Using 56 anatomical landmarks, 20 angles and 155 distances were measured. MEDAS software was used for performing connected and unconnected t-tests and Spearman´s rank correlation test to evaluate interrelations and differences. Results Orbital anatomy was highly symmetrical with a mean side difference of 0.3 mm for distances and 0.6° for angles. There was a small albeit statistically significant difference in 13 out of 155 distances in women and 1 in men concerning patients with and without EO. Two out of 12 angles showed a statistically significant difference between female patients with and without EO. Regarding sex, statistically significant differences occurred in 39 distances, orbit volume, orbit surface, and 2 angles. On average, measurements were larger in men. Concerning globe position within the orbit, larger distances to the orbital apex correlated with larger orbital dimensions whereas the sagittal position of the orbital rim defined Hertel values. Conclusion In this study, little difference in orbital anatomy between patients with and without EO was found. Concerning sex, orbital anatomy differed significantly with men presenting larger orbital dimensions. Regarding clinically measured exophthalmos, orbital aperture anatomy is an important factor which has to be considered in distinguishing between true exophthalmos with a larger distance between globe and orbital apex and pseudoexophthalmos were only the orbital rim is retruded. Thus, orbital anatomy may influence therapy regarding timing and surgical procedures as it affects exophthalmos.